Answer:
For a polynomial of the form ax2+bx+c a x 2 + b x + c , rewrite the middle term as a sum of two terms whose product is a⋅c=2⋅−2=−4 a ⋅ c = 2 ⋅ - 2 = - 4 and whose sum is b=−3 b = - 3 . Factor −3 - 3 out of −3x - 3 x .
Step-by-step explanation:
Answer: =(x - 1) x (x^2 + x + 1)
Answer:
Graph A is correct
Step-by-step explanation:
p(x)= x/10
x= 1, 2, 3, 4
Plug in x values in p(x)
when x=1 , then P(1) = 1/10
When x=2 , then P(2) = 2/10
When x=3 , then P(3) = 3/10
When x=4 , then P(4) = 4/10
In the graph y axis has 2/10 , 4/10 , 6/10...
1/10 lies between 0 and 2/10
3/10 lies between 2/10 and 4/10
Graph A is correct
Answer:
3x-13+2x+4=116( the sum of two interior angle is epual to the sum of exterior angle )
5x =116-9
5x=107
x=21.4 degree
then
angle a= 3*21.4-13
a=51.2degree
angle b=2*21.4+2
b =44.8degree
Step-by-step explanation:
plz make me brainliest
Answer is d
Step-by-step explanation:
If you multiply a^6 and a it equals a^7